2011
DOI: 10.1080/02699931.2010.516905
|View full text |Cite
|
Sign up to set email alerts
|

Contextual interference processing during fast categorisations of facial expressions

Abstract: We examined interference effects of emotionally associated background colours during fast valence categorisations of negative, neutral and positive expressions. According to implicitly learned colour-emotion associations, facial expressions were presented with colours that either matched the valence of these expressions or not. Experiment 1 included infrequent non-matching trials and Experiment 2 a balanced ratio of matching and non-matching trials. Besides general modulatory effects of contextual features on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…Within this framework, color can be regarded as one such source of contextual information, and thus as an implicit affective cue ( Friedman and Förster, 2010 ). Researchers have therefore recently examined how color is subjectively associated with emotional faces ( Palmer et al, 2013 ) or used as an implicit source of contextual information for faces ( Frühholz et al, 2011 ; Young et al, 2013 ; Gil and Le Bigot, 2014 ). Regarding red, Palmer et al (2013) , Experiment 2 found that when participants had to choose the color (out of possible 37) that was the most/least consistent with an emotional face, angry faces were particularly closely associated with reddish colors.…”
Section: Introductionmentioning
confidence: 99%
“…Within this framework, color can be regarded as one such source of contextual information, and thus as an implicit affective cue ( Friedman and Förster, 2010 ). Researchers have therefore recently examined how color is subjectively associated with emotional faces ( Palmer et al, 2013 ) or used as an implicit source of contextual information for faces ( Frühholz et al, 2011 ; Young et al, 2013 ; Gil and Le Bigot, 2014 ). Regarding red, Palmer et al (2013) , Experiment 2 found that when participants had to choose the color (out of possible 37) that was the most/least consistent with an emotional face, angry faces were particularly closely associated with reddish colors.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, they failed to show that green facilitates the categorization of happy ones. Frühholz and colleagues (2011) examined the impact of color on the recognition of facial expressions of fear, happiness and neutrality, after participants had undergone a learning phase designed to artificially induce a specific association between color and emotion (Experiments 1 and 2) [49] . Importantly for our purpose, the authors stressed that the face–color associations they created were not random, but based on shared emotional properties (i.e., arousal and valence).…”
Section: Introductionmentioning
confidence: 99%
“…Studies convincingly show that the task specific context can influence the associative meaning of a concept in a task (e.g., Blair 2002;Elliot & Maier, 2014;Frühholz, Trautmann-Lengsfeld, & Herrmann, 2011;Lakens, Fockenberg, Lemmens, Ham, & Midden, 2013). For example, studies suggest that in an achievement context, red is associated with failure and negativity (e.g., Moller, Elliot, & Maier, 2009), while in a romantic context, red is associated with attraction and excitement (e.g., Elliot & Pazda, 2012).…”
mentioning
confidence: 99%